A study on effect of neoadjuvant chemotherapy on peri operative complications and outcome in patients under-going radical cystectomy for muscle invasive bladder cancer - Das, Ranjit Kumar; Agrawal, Vishnu; Khan, Dawood; Dey, Ranjan Kumar; Khan, Imran Ahmad; Basu, Supriya (International Journal of Research in Medical Sciences, 2018)
Background: To compare the peri-operative complications, related to radical cystectomy and to compare peri operative outcomes between patients receiving neoadjuvant chemotherapy and those treated with radical cystectomy alone. Methods: This was prospective observational study. The study was conducted at ‘The Department of Urosurgery, R. G. Kar Medical College and Hospital, Kolkata’. Study period was between March 2016 to March 2018. Total 36 patients were included in present study. Patients after clinical diagnosis and risk factor profile analysis were divided into two groups: (1) radical cystectomy alone (n=24) (2) patients received neoadjuvant chemotherapy (gemcitabine and cisplatin regime) followed by radical cystectomy (n=12). Different parameters were compared. Results: Total 36 patients were underwent radical cystectomy. In group 1, 96% (n=23) were having T2 stage while 4% (n=1) were having T3stage. In group 2 25% (n=3) patients were having T2stage while 75% (n=9) were having T3 stage as per CECT staging. There were no significant difference noted in perioperative complications in both groups except perioperative adhesions (group 2, 47% vs group 1, 8.3%). There was significant time delay in radical cystectomy in group 2 (patients received neoadjuvant chemotherapy). Conclusions: We found there were no significant increase in perioperative morbidity and mortality with Neoadjuvant Chemotherapy. Most of the complications were comparable to previous studies.